A Stable Solid Electrolyte Interphase for Magnesium Metal Anode Evolved from a Bulky Anion Lithium Salt. Issue 6 (18th December 2019) - Tang, Kun; Du, Aobing; Dong, Shanmu; Cui, Zili; Liu, Xin; Lu, Chenglong; Zhao, Jingwen; Zhou, Xinhong; Cui, Guanglei
Abstract: Rechargeable magnesium (Mg) metal batteries are a promising candidate for "post‐Li‐ion batteries" due to their high capacity, high abundance, and most importantly, highly reversible and dendrite‐free Mg metal anode. However, the formation of passivating surface film rather than Mg 2+ ‐conducting solid electrolyte interphase (SEI) on Mg anode surface has always restricted the development of rechargeable Mg batteries. A stable SEI is constructed on the surface of Mg metal anode by the partial decomposition of a pristine Li electrolyte in the electrochemical process. This Li electrolyte is easily prepared by dissolving lithium tetrakis(hexafluoroisopropyloxy)borate (Li[B(hfip)4 ]) in dimethoxyethane. It is noteworthy that Mg 2+ can be directly introduced into this Li electrolyte during the initial electrochemical cycles for in situ forming a hybrid Mg 2+ /Li + electrolyte, and then the cycled electrolyte can conduct Mg‐ion smoothly. The existence of this as‐formed SEI blocks the further parasitic reaction of Mg metal anode with electrolyte and enables this electrolyte enduring long‐term electrochemical cycles stably. This approach of constructing superior SEI on Mg anode surface and exploiting novel Mg electrolyte provides a new avenue for practical application of high‐performance rechargeable Mg batteries. Abstract : A stable Li‐species‐containing solid electrolyte interphase is constructed on the surface of a Mg metal anode by the partial decomposition of a pristine Li electrolyte in the electrochemical process. The existence of this as‐formed solid electrolyte interphase blocks the further parasitic reaction of the Mg metal anode with the electrolyte and allows this electrolyte to endure long‐term electrochemical cycles stably.